The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2017
DOI: 10.1007/s11250-017-1490-6
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors of Japanese encephalitis virus (JEV) in livestock and companion animal in high-risk areas in Malaysia

Abstract: Japanese encephalitis (JE) is vector-borne zoonotic disease which causes encephalitis in humans and horses. Clinical signs for Japanese encephalitis virus (JEV) infection are not clearly evident in the majority of affected animals. In Malaysia, information on the prevalence of JEV infection has not been established. Thus, a cross-sectional study was conducted during two periods, December 2015 to January 2016 and March to August in 2016, to determine the prevalence and risk factors in JEV infections among anima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 36 publications
(47 reference statements)
1
28
0
Order By: Relevance
“…For this reason, JEV seroprevalence studies were mainly conducted in swine reared in (or close to) such ecosystems. In such contexts, JEV seroprevalence was shown to be potentially very high, with values ranging from about 40% in Indonesia to more than 75% of HIA- or ELISA-positive results (confirmed by SNT) in Hong Kong or Laos [31,34,84,85,89,101,103,104,116]. These high prevalence levels led to JE being considered mainly a rural disease, and proximity to rice fields and pig rearing, particularly backyard farming, were identified as major risk factors of JE in humans [89].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For this reason, JEV seroprevalence studies were mainly conducted in swine reared in (or close to) such ecosystems. In such contexts, JEV seroprevalence was shown to be potentially very high, with values ranging from about 40% in Indonesia to more than 75% of HIA- or ELISA-positive results (confirmed by SNT) in Hong Kong or Laos [31,34,84,85,89,101,103,104,116]. These high prevalence levels led to JE being considered mainly a rural disease, and proximity to rice fields and pig rearing, particularly backyard farming, were identified as major risk factors of JE in humans [89].…”
Section: Resultsmentioning
confidence: 99%
“…However, several studies conducted in Taiwan [116], Thailand [14,81], Hong Kong [84], Japan [128], and more recently in Cambodia [74,75], Vietnam [113,115], and Malaysia [31] showed that JEV can also circulate in swine in peri-urban or even urban areas. The JEV seroprevalence values ranged from 26.5% to more than 90% of HIA- or IgG ELISA-positive results in cross-sectional studies, and seroconversion rates reached 100% of the monitored piglets in longitudinal studies performed in Cambodia.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is similar to the findings of other JEV seroprevalence studies in Southeast Asia. In Bali (Indonesia) 20.6% of ducks and 36.7% of chickens were tested positive (37), and a study in Malaysia found 28.9% of the tested domestic birds positive for JEV antibodies (38). In addition, several experimental studies showed that domestic birds can be infected with JEV (5,14,15) and might even act as JEV reservoirs (39,40).…”
Section: Discussionmentioning
confidence: 99%
“…Japanese encephalitis virus most commonly circulates amongst birds and mosquitoes 30. Pigs are referred to as a virus-amplifying host because they develop high viremia 31.…”
Section: Prevalence and Distributionmentioning
confidence: 99%